Entirely Anatolian Hydrobiid (Caenogastropoda–Truncatelloidea–Hydrobiidae) Clade Revisited: Two More New Genera and Six New Species † - Jaszczy?ska, Aleksandra; Hofman, Sebastian; Odabaşi, Deniz Anıl; Ekín, İhsan; Sîrbu, Ioan; Falniowski, Andrzej (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Previous studies identified a clade of the Hydrobiidae endemic to Anatolia, with no closer relationships with the European snails, despite close relations between the fauna of these two regions. Three genera—each monotypic: Sheitanok Schütt et Şeşen, 1991, Anadoludamnicola Şahin, Koca et Yıldırım, 2012, and Kozanium Odabaşı et Falniowski, 2025—belonged to this clade. Our study describes the Hydrobiidae collected at five springs in Anatolia. Shell morphology and biometry, radulae, soft parts pigmentation, female reproductive organs, and penes are described and illustrated. Cytochrome oxidase subunit I (COI) sequences have been used to infer phylogenetic relationships and species distinctness of these snails. An integrative taxonomic approach resulted in the distinction of six species new to science. One of them belonged to the genus Sheitanok, another one to Anadoludamnicola. The other four species are clustered into two genera not described thus far, and the offered names are Dicle and Adaniya. It is noteworthy that three species recognized within one of these genera were clearly demarcated both molecularly and morphologically (morphological differences were higher than typical of the hydrobiid congeners). However, two of the three techniques of species delimitation based on the molecular sequences did not confirm their distinctness. This stresses the necessity of a holistic approach in the truncatelloid taxonomy. © 2025 by the authors.
Keywords: cytochrome oxidase; integrative taxonomy; morphology vs. molecules; species delimitation